Kinetics and Mechanism of Hydrolysis of N-(2'-Hydroxyphenyl)phthalamic Acid (1) and N-(2'-Methoxyphenyl)phthalamic Acid (2) in a highly alkaline medium - Ariffin, Azhar; Khan, M.N.; Sim, Y.L.; Damit, E.F. (2009)
A kinetic study on hydrolysis of N-(2'-hydroxyphenyl)phthalamic acid (1), N-(2'-methoxyphenyl)phthalamic acid (2), and N-(2'-methoxyphenyl)benzamide (3) under a highly alkaline medium gives second-order rate constants, k(OH), for the reactions of HO(-) with 1, 2, and 3 as (4.73 +/- 0.36) x 10(-8) at 35 degrees C, (2.42 +/- 0.28) x 10(-6) and (5.94 +/- 0.23) x 10(-5) M(-1) s(-1) at 65 degrees C, respectively. Similar values of k(OH) for 3, N-methylbenzanilide, N-methylbenzamide, and N,N-dimethylbenzamide despite the difference between pK(a) values of aniline and ammonia of similar to 10 pK units are qualitatively explained. (C) 2008 Wiley Periodicals, Inc, Int | Chem Kinet 41: 1-11, 2009